Kedudukan Hukum Tradisi Adat Keduhei pada Perkawinan Masyarakat Desa Sebukar Kabupaten Kerinci - Madani, Ahmad; Rembrandt, Rembrandt; Yasniwati, Yasniwati (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2025)
The customary practice of keduhei sudih kawan in traditional marriage ceremonies in Sebukar Village is considered a fundamental and mandatory ritual. However, there are no positive legal norms that explicitly recognize customary traditions as formal requirements for the validity of marriage. This study aims to examine the legal status and provide a juridical analysis of the keduhei tradition in the context of Indonesian customary law. This study employs an empirical juridical approach, utilizing data collection methods that include observation and in-depth interviews with members of the Sebukar Village Customary Council (Lembaga Kerapatan Adat Desa, LKAD). This research is prescriptive, with data processed systematically through editing and analyzed qualitatively. The results show that keduhei not only functions as a complement to the ceremony but also as an important legal affirmation in marriage based on customary norms, so it has a strong legal position. However, some elements of the custom, such as certain requirements and sanctions, can conflict with the provisions of national law, so a balance between customary law and national law is needed to ensure its sustainability and legal coherence.